Pengaruh Literasi Halal, Kampanye Wajib Halal Oktober (WHO) 2024, Dan Program SEHATI Terhadap Minat Daftar Sertifikasi Halal (Studi Kasus Pada UMKM di Kota Malang) - Safitri, Anisa Maulidia; Wahono, Budi; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze and identify the influence of halal literacy, the Mandatory Halal October (WHO) 2024 campaign, and the SEHATI program on the interest in halal certification registration among MSMEs in Malang City. The population of this study includes micro, small, and medium enterprises in Malang City engaged in the culinary field. The research method used is quantitative with a multiple linear regression model. The sample consisted of 85 respondents selected using a non-probability sampling technique, namely purposive sampling, with the criteria of culinary MSME actors in Malang City who have attended halal socialization at least once and participated in the free halal certification program (SEHATI). Data analysis was conducted with the help of IBM SPSS 30 software. The research results show that based on the F test, the calculated F value > table F value (64.954 > 1.664), thus the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. This indicates that simultaneously, the variables of halal literacy, the Mandatory Halal October (WHO) 2024 campaign, and the SEHATI program have a positive and significant impact on the interest in registering for halal certification. Partially, the t-test shows that the WHO 2024 campaign has a positive and significant impact on the interest in halal certification registration, while halal literacy has a significant but negative impact on that interest. Additionally, the coefficient of determination value of 69.5% indicates that the halal literacy variable, the WHO 2024 campaign, and the SEHATI program can explain the interest in halal certification registration, while the remaining 30.5% is influenced by other factors not discussed in this study.    Keywords: Interest in Halal Certification Registration, Halal Literacy, Mandatory Halal October Campaign (WHO) 2024, SEHATI Program, MSMEs